2009
DOI: 10.1007/s00412-009-0219-3
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear envelope-limited chromatin sheets (ELCS) and heterochromatin higher order structure

Abstract: The interphase nucleus and nuclear envelope can acquire a myriad of shapes in normal or pathological cell states. There exist a wide variety of indentations and invaginations, of protrusions and evaginations. It has been difficult to classify and name all of these nuclear shapes and, consequently, a barrier to understanding the biochemical and biophysical causes. This review focuses upon one type of nuclear envelope shape change, named "nuclear envelope-limited chromatin sheets" (ELCS), which appears to involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 91 publications
5
36
0
Order By: Relevance
“…7) clearly demonstrates the presence of the epichromatin epitope within the condensed heterochromatic region adjacent to the nuclear envelope, as well as within the single heterochromatic layer of ELCS. 5 These images prove that the epichromatin epitope does include peripheral heterochromatin. However, it is becoming increasingly clear that some transcriptionally-active euchromatin can be localized near the nuclear envelope.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…7) clearly demonstrates the presence of the epichromatin epitope within the condensed heterochromatic region adjacent to the nuclear envelope, as well as within the single heterochromatic layer of ELCS. 5 These images prove that the epichromatin epitope does include peripheral heterochromatin. However, it is becoming increasingly clear that some transcriptionally-active euchromatin can be localized near the nuclear envelope.…”
Section: Discussionmentioning
confidence: 80%
“…Describing these principles is a major goal of cell biology and encompasses understanding the interphase nucleus, the mitotic chromosome and other chromatin structural states. [1][2][3][4][5] A major advance in our understanding of the organization of chromatin came with the description of chromosome territories (CTs), 6,7 which demonstrated that the individuality of mitotic chromosomes is preserved, albeit in a swollen form, within the interphase nucleus. Evidence has also been presented that within these territories chromatin exists in "knot-free" globules, analogous to the nucleosomal "beads-on-a-string"; but at…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…53,70,71 However, there must be functional redundancy, since homozygous ic EPRO cells are deficient in LBR but can still divide (and differentiate) in vitro. 85,87 Our speculation that LBR is involved with NE membrane growth is based upon our studies with granulocytic cells differentiation in vitro and in vivo: (1) a positive correlation was observed between increased LBR levels in HL-60 cells, appearance of nuclear lobulation and formation of ELCS; 81,82,89 (2) a or intranuclear membranes. High levels of expression of GFP-lamins (not including lamin C) lead to extensive intranuclear membranes.…”
Section: Conundrums and Speculationsmentioning
confidence: 90%
“…88 In the absence of sufficient LBR, the differentiated granulocyte nuclei are ovoid, appear to have a reduced NE surface area, and the heterochromatin redistributes towards the center of the nucleus. [84][85][86] In vitro granulopoiesis of the human acute myeloid leukemia cells (HL-60) with retinoic acid results in a marked increase of LBR content and nuclear lobulation with an exaggerated growth of the NE into sheets (nuclear envelope-limited chromatin sheets, or "ELCS" 81,89 ). It should also be mentioned that overexpression of the C-terminal region of LBR following transfection of HeLa cells results in perinuclear aggregates, stacks of overproduced membranes pinched off the NE, 51 which are devoid of lamin B.…”
Section: Lbr Influences On Nuclear Shape and Heterochromatin Distribumentioning
confidence: 99%